Macrophage infection, activation, and histopathological findings in ebolavirus infection - Wanninger, Timothy G.; Millian, Daniel E.; Saldarriaga, Omar A.; Maruyama, Junki; Saito, Takeshi; Reyna, Rachel A.; Taniguchi, Satoshi; Arroyave, Esteban; Connolly, Melanie E.; Stevenson, Heather L.; Paessler, Slobodan (Frontiers in Cellular and Infection Microbiology, 2022)
Macrophages contribute to Ebola virus disease through their susceptibility to direct infection, their multi-faceted response to ebolaviruses, and their association with pathological findings in tissues throughout the body. Viral attachment and entry factors, as well as the more recently described influence of cell polarization, shape macrophage susceptibility to direct infection. Moreover, the study of Toll-like receptor 4 and the RIG-I-like receptor pathway in the macrophage response to ebolaviruses highlight important immune signaling pathways contributing to the breadth of macrophage responses. Lastly, the deep histopathological catalogue of macrophage involvement across numerous tissues during infection has been enriched by descriptions of tissues involved in sequelae following acute infection, including: the eye, joints, and the nervous system. Building upon this knowledge base, future opportunities include characterization of macrophage phenotypes beneficial or deleterious to survival, delineation of the specific roles macrophages play in pathological lesion development in affected tissues, and the creation of macrophage-specific therapeutics enhancing the beneficial activities and reducing the deleterious contributions of macrophages to the outcome of Ebola virus disease.